Impact of Soil Moisture on the Efficacy and Reproductive Success of Entomopathogenic Nematodes Against Insect Hosts - Chantab, Kanjana; Khueamee, Aekkachai; Jampahway, Suphat; Thodthasri, Saiphon; Ngamhui, Nion (วารสารผลิตกรรมการเกษตร, 2026)
Entomopathogenic nematodes (EPNs), specifically Steinernema siamkayai, are effective biological control agents for managing pests due to their ability to target and eliminate a variety of insect hosts without harming non-target organisms. However, their efficacy is influenced by environmental factors, particularly soil moisture. This study evaluated the impact of different soil moisture levels on mortality rates and nematode reproduction of mealworms (Tenebrio molitor) and Greater wax moth (GWM) (Galleria mellonella), both in the presence (+) and absence (–) of S. siamkayai. The mortality data indicated that GWM larvae had significantly higher mortality rates compared to mealworms when exposed to S. siamkayai. The mortality rate of GWM larvae increased with higher soil moisture levels, except at 20%. The highest mortality rate (80%) was observed at 15% soil moisture. While mealworms showed increasing mortality rates with higher soil moisture, their overall mortality was lower compared to GWM larvae. Both mealworms and GWM larvae exhibited higher mortality rates when exposed to S. siamkayai. Reproduction success of EPNs was assessed by dissecting the host larvae and counting the number of nematodes present. The highest reproduction rate was observed at a soil moisture level of 15%, with 379 nematodes in mealworms and 471 nematodes in GWM. This indicated that 15% soil moisture provides optimal conditions for nematode survival and reproduction. Conversely, the drop in mortality rate at 20% soil moisture suggested that excessively high moisture levels may negatively impact S. siamkayai activity or survival. Both extremely low and high moisture levels negatively affected nematode reproduction. Maintaining appropriate soil moisture levels is crucial for optimizing the effectiveness of S. siamkaya in biological pest control strategies. Ensuring that the soil moisture is around 15% can significantly enhance nematode survival, reproduction, and subsequent pest elimination capabilities.